2011
DOI: 10.3166/rfg.211.81-92
|View full text |Cite
|
Sign up to set email alerts
|

Balanced scorecard et pilotage de la responsabilité sociale de l´entreprise. Retour d´expérience

Abstract: Distribution électronique Cairn.info pour Lavoisier. © Lavoisier. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…The study by Meyssonnier and Rasolofo-Distler (2011) should also be mentioned. The authors identified the nature of the balanced scorecard (BSC) by means of a field study on CSR implementation, which was carried out over a three-year period and resulted in annual strategic panel and monthly reports.…”
Section: Strategic Models Of Corporate Social Responsibilitymentioning
confidence: 99%
“…The study by Meyssonnier and Rasolofo-Distler (2011) should also be mentioned. The authors identified the nature of the balanced scorecard (BSC) by means of a field study on CSR implementation, which was carried out over a three-year period and resulted in annual strategic panel and monthly reports.…”
Section: Strategic Models Of Corporate Social Responsibilitymentioning
confidence: 99%
“…In our case, it is a 3-year longitudinal study concerning the design and implementation of a BSC by the largest real estate agent in eastern France. This study has already resulted in scientific publications (Meyssonnier & Rasolofo-Distler, 2011;Rasolofo-Distler, 2009;Rasolofo-Distler & Zawadzki, 2013). However, this is the first time that the case will be analysed from the SSC management angle.…”
Section: Rental Management Of Housing Inmentioning
confidence: 99%
“…Mêlant des critères d'évaluation quantitatifs et qualitatifs, le BSC a une portée d'action à la fois dans le présent et le futur (Choffel et Meyssonnier, 2005). Dans le cadre de ses développements, des dimensions de durabilité ont été ajoutées aux quatre dimensions de mesure de performance de l'entreprise que prenait initialement en compte l'outil (performance financière, performance vis-à-vis des clients, performance opérationnelle, capacité d'innovation et d'apprentissage) (Naro et Noguera, 2008 ;Meyssonnier et Rasolofo-Distler, 2011).…”
Section: Enjeux Du Pilotage De La Performance De Durabilité Dans Une ...unclassified